High-throughput screening identifies a critical role of the SPOP–PABPC1 axis in lung adenocarcinoma progression - Jiahui Zhang; Ran Liu; Xue Han; Yutong Jiao; Yun Peng; Zizhang Zhou; Yanran Deng; Lianggeng Gong (Proceedings of the National Academy of Sciences, 2026)
Lung adenocarcinoma (LUAD) is the most common and deadly subtype of lung cancer, with limited therapeutic options and poor prognosis. Ubiquitination is an important posttranslational modification (PTM) that controls protein turnover, localization and interaction. The dysregulated ubiquitination machinery is a hallmark of cancer, contributing to tumor development. Identifying key E3 ubiquitin ligases and deubiquitinases in LUAD could lead to new biomarkers and treatments. Through RNA sequencing, bioinformatics, and clinical studies, SPOP has been identified as a promising E3 ligase target in LUAD. SPOP is downregulated in LUAD samples and associated with poorer patient outcomes. Functional analyses demonstrate that SPOP suppresses LUAD cell migration, proliferation, and in vivo tumor growth. Mechanistically, SPOP targets poly(A)-binding protein cytoplasmic 1 (PABPC1) for nonproteolytic ubiquitination, leading to its nuclear retention and inhibition of global protein synthesis, thereby suppressing the oncogenic effects of PABPC1. Furthermore, the deubiquitinase HAUSP is able to counteract SPOP-mediated ubiquitination of PABPC1, enhancing its oncogenic role in LUAD cells. Collectively, our findings reveal a SPOP/HAUSP-PABPC1 regulatory axis in LUAD, where SPOP and HAUSP oppositely modulate PABPC1 ubiquitination to control LUAD cell proliferation and migration. This axis represents a promising therapeutic target in LUAD.